Analisa Tingkat Perbedaan Harga Pada Pelaksanaan Program Percepatan Peningkatan Tata Guna Air Irigasi (P3-Tgai) Berdasarkan Usulan Biaya (SK Gubernur Provinsi Jambi) Dan Harga Survei Toko (Studi Kasus: Proyek Saluran Irigasi P3A Maju Jaya Desa Sembubuk - DF, Dian Wahyoni; Vitri, Gusni; Zayu, Wiwin Putri (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
P3-TGAI is a cash-intensive program from the Ministry of Public Works and Public Housing with APBN funds to support one of the development priority agendas contained in the 2020-2025 RPJM, namely strengthening infrastructure aimed at supporting economic activity and encouraging equitable national development. This research was conducted in the construction of P3A Maju Jaya irrigation canal, Sembubuk Village, Muaro Jambi Regency in the recipient of the Acceleration of Irrigation Water Use Improvement Program (P3-TGAI). The purpose of this study was to determine the difference in costs applied in the field with the standard regulations of the Governor of Jambi Province, the type of research used is mixed method. The data analysis technique method used for data processing is the usual Excel calculation method. The results showed that the irrigation channel of P3A Maju Jaya, Sembubuk Village, Muaro Jambi Regency if done using the shop survey price, the volume length of the channel is greater than using the price of the Jambi Provincial Governor's regulation, where for the channel work with a fund of Rp. 195,000,000 if done using the shop survey price, the volume length of the channel can be obtained up to 290 m.